THE DEVELOPMENT OF ‘AIDDA’ SOCIALIZATION MODEL (AWARENESS, INTEREST, DESIRE, DECISION AND ACTION) TO STOP VIOLENCE AGAINST CHILDREN IN RONGGA DISTRICT, BANDUNG REGION - Budimansyah, Dasim (UPI Press, 2014)
Methodologically, this research employed Research and Development methods toimplementation of the AIDDA model as an effective legal socialization. It was conductedin five villages involving RT/ RW leaders, chiefs of village, and heads of households whowere residents within the Pos Pemberdayaan Keluarga (Posdaya) Rongga district, BandungRegion. Research findings show that society in Rongga district held similar perspectives of therights and obligations of children and parents, with prior knowledge related to nurturing socialawareness. AIDDA in law socialization is achieved through two phases comprising of directlegal obligations for civilization and indirect through legal socialization. The socializationon violence against children was considered across the geographical location of the researchsite by provision of a form, which collaborated with the AIDDA method, hence resulting inhouseholds with high legal awareness. The presentation of AIDDA model was organized inaccordance to the materials, methods, media/ source and awareness-value based evaluation.The values on both direct and indirect law socialization were emphasized on awareness ofvalues on respective societies with the assistance of law experts. In this sense, there was asignificant positive effect of 38% on the development on AIDDA model in legal socializationtowards the quality of socialization in reshaping the society’s law awareness.Keyword: Violence against children, socialization model, AIDDA (Awareness, Interest,Desire, Decision, Action)